(untitled) (The Conference Hub, 2025)
Shuhrat’s work “Golden Stainless” was created in the 1960s. The work depicts scenes of war, hardships behind the front lines, human psychology, character, and social problems in the family. This article analyzes the qualities of a true Uzbek woman: loyalty, love, courage, fortitude, boundless devotion to her husband, and the image of Jannat, who patiently overcomes the dark days of grief.